Prognostic Value of Peripheral Whole Blood Cell Counts Derived Indexes in Gallbladder Carcinoma: A Systematic Review and Meta-Analysis - Xu, Bowen; Chen, Zhiqiang; Zhang, Jing; Chang, Jianhua; Zhao, Wei; Dong, Zhaoru; Zhi, Xuting; Li, Tao (Frontiers in Oncology, 2021)
Background Gallbladder carcinoma (GBC) is a rare gastrointestinal malignancy with poor prognosis. Adequate pre-treatment prediction of survival is essential for risk stratification and patient selection for aggressive surgery or adjuvant therapeutic strategy. Whole blood cell count (WBCC) derived indexes are broadly used as prognosticative biomarkers in various cancer types, but their utility in GBC needs to be validated. Methods An extensive literature review was conducted in line with PRISMA guideline until June 31 2020, to identify original studies concerning WBCC-derived indexes as prognostic indicators in GBC. All relative parameters were extracted and pooled for statistical analyses. Results Fourteen studies incorporating 2324 patients were included with a high quality and low risk of biases. All 14 studies evaluated the prognostic value of NLR showing a significant correlation with OS in GBC patients (HR=1.94, P<0.001). And elevated NLR was revealed to corelate with TNM stage (stage III and IV, OR=4.65, P<0.001), tumor differentiation (OR=2.37, P<0.042), CA 19-9 (SMD=0.47, P=0.01), but no significance was found with age, sex and CEA. Positive indicative value of MLR and PLR were also confirmed with a HR of 2.06 (P<0.001) and 1.34 (P<0.001), respectively. Conclusion The WBCC-derived indexes including NLR, MLR/LMR and PLR were validated to be useful prognostic parameters for predicting survival outcomes in GBC patients. These series of indexes, especially NLR, could improve risk stratification and facilitate better patient selection for surgical resection or aggressive chemotherapy in the decision making of GBC patients.